Experiments in financial economics - Collins, Sean M. 1983-; Isaac, R. Mark 1954-; Norton, Douglas A., 1984- (Research in experimental economics, 2013)
Research in experimental economics focuses on laboratory experimental economics, but welcomes work from authors of theoretical, empirical, or field economic research if it would be of interest to the broader experimental economics community. The goal of Research in Experimental Economics is to be complementary with, and not in competition with, traditional journals as outlets for experimental work. Research in Experimental Economics has the freedom to consider papers that may not be appropriate for traditional journals for a variety of reasons. Some examples of these strengths include: theme volumes, replication studies, research which requires longer manuscripts for presentation of data or analysis, and papers on methodological topics. The volumes of Research in Experimental Economics are not tied to specific, recurring conferences. Typically, a volume theme is established with scholars who are willing to serve as volume-specific editors. The only constraint the senior editor places on the volume editors is that the papers should undergo a formal referee process using the same quality standards as traditional journals. Recent topics have included market power, charitable contributions, and field experiments.